Islamic Social Finance Solutions To Housing Unaffordability For Middle And Lower-Income Households In China - Yaxin, Ma (2022)
Since reform and opening, China’s economic growth has accelerated from a plan-controlled to a market-led process. People’s living conditions have been greatly improved. However, home prices have deviated from their normal trajectory due to excess fiat money supply and housing supply and demand issues (among other factors), making it difficult for many middle- and low-income households to own their own homes and spawning an array of housing-related socioeconomic problems. Although the Chinese government has attempted house price control policies for an extended period, the impact has been little. This circumstance is not unique to China, but the sheer quantity of China’s population exacerbates it. This research combines the best tested and proven housing work examples from the other parts of the world (Musharakah Mutanaqisah, Ameen housing Cooperate, and EthisCrowd) and proposes a collaborative solution with Islamic finance as the main principle. In order to observe whether Chinese households (minority Muslims and most non-Muslims) accept the proposed model, and to seek an assessment of the applicability of the proposed model in the real world from finance and real estate business experts, the author conducted mixed method approach which includes quantitative and qualitative.